Population exposure to trace elements in the Kilembe copper mine area, Western Uganda: a pilot study - Mwesigye, Abraham R.; Young, Scott D.; Bailey, Elizabeth H.; Tumwebaze, Susan B. (Elsevier, 2016)
The mining and processing of copper in Kilembe, Western Uganda, from 1956 to 1982 left over 15 Mt. of tailings containing cupriferous and cobaltiferous pyrite dumped within a mountain river valley. This pilot study was conducted to assess the nature and extent of risk to local populations from metal contamination arising from those mining activities. We determined trace element concentrations in mine tailings, soils, locally cultivated foods,house dust, drinking water and human biomarkers (toenails) using ICP-MS analysis of acid digested samples. The results showed that tailings, containing higher concentrations of Co, Cu, Ni and As compared with world average crust values had eroded and contaminated local soils. Pollution load indices revealed that 51% of agricultural soils sampled were contaminated with trace elements. Local water supplies were contaminated, with Co concentrations that exceeded Wisconsin (US) thresholds in 25% of domestic water supplies and 40% of Nyamwamba river water samples. Zinc exceeded WHO/FAO thresholds of 99.4 mg kg−1 in 36% of Amaranthus vegetable samples, Cu exceeded EC thresholds of 20 mg kg−1 in 19% of Amaranthus while Pb exceeded WHO thresholds of 0.3 mg kg−1 in 47% of Amaranthus vegetables. In bananas, 20% of samples contained Pb concentrations that exceeded the WHO/FAO recommended threshold of 0.3 mg kg−1. However, risk assessment of local foods and water, based on hazard quotients (HQ values) revealed no potential health effects. The high external contamination of volunteers' toenails with some elements (even after a washing process) calls into question their use as a biomarker for metal exposure in human populations where feet are frequently exposed to soil.